A Perspective on Rehabilitation Through Open-Source Low-Cost 3D-Printed Distal to the Wrist Joint Transitional Prosthetics: Towards Autonomous Hybrid Devices - Florin-Felix Răduică; Ionel Simion; Ioana-Cătălina Enache; Elena Narcisa Valter; Alessandro Naddeo (Machines)
Over the years, patients with partial hand loss have relied on expensive prosthetics to recover some of the hand functionality. Fortunately, advancements in additive manufacturing desktop solutions allow transitional prosthetics prices to decrease. Therefore, the present work focused on providing a basic overview of the field and available low-cost 3D-printed upper-limb prosthetic devices. The aim was to develop a basic frame of reference on the field of transitional partial hand prosthetics. Concomitantly, this study also highlights additive manufacturing techniques on which further research can be done whilst helping to provide a new variant for an upper limb prosthetic device. The initial stages, current practices, and future possibilities were considered. Researchers and industry can utilize these findings to develop additional variants for the benefit of patients suffering from partial hand loss.